The correct answers are
84 and 54
:)
B=(xy + x)(xy + x)
C=(2x – 3)(–3 + 2x)
D=(16 – x2)(x2 – 16)
E=(4y2 + 25)(25 + 4y2)
The correct answers are:
B=(xy + x)(xy + x) ; C=(2x – 3)(–3 + 2x) ; and E=(4y² + 25)(25 + 4y²)
Explanation:
In order to have a perfect square trinomial, we must multiply two binomials that are exactly the same. For (xy+x)(xy+x), are multiplying two identical binomials.
For (2x-3)(-3+2x), we are multiplying two binomials that are the same but written in a different order. The same is true of (4y² + 25)(25 + 4y²).
Answer:
A and E and C
Step-by-step explanation:
A perfect square trinomial can be written as the square of a binomial.
Please help!! I got to the last part of the equation and now I'm lost.
Isolate the variable by dividing each side by factors that don't contain the variable.
Exact Form:
p = −33/13
Decimal Form:
p = −2.¯538461 (terminating)
Mixed Number Form:
p = −2/7/13
9x+2=3x-10
3(x-2)=-2(x+3)
Answer:
The new balance is $45.97 .
Step-by-step explanation:
As given
Your bank balance is $102.35 and you've just made purchases for $20, $33.33, and $52.80.
Bank balance after the purchase = $102.35 - $20 -$33.33 - $52.80
= $102.35 - $ 106.13
= - $3.78
As given
You then make deposits of $25 and $24.75.
Total deposit money = $25 + $24.75
= $49.75
Thus
New balance = Bank balance after the purchase + Total deposit money
= - $3.78 + $49.75
= $ 45.97
Therefore the new balance is $45.97 .